2017
DOI: 10.1155/2017/7929671
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia and Urinary Tract Infection Caused byChromobacterium violaceum: Case Reports from a Tertiary Care Hospital in Kathmandu, Nepal

Abstract: Chromobacterium violaceum is ubiquitous in the environment of tropical and subtropical regions but the infections caused by this organism are rare and the urinary tract infections caused by it are even rarer. Due to the propensity for hematogenous spread leading to fatal sepsis, the infections caused by Chromobacterium violaceum have high mortality rate (65–80%) with death occurring in as less as one week of acquiring infection. So, prompt proper treatment is necessary for successful treatment of the infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“… 2 Furthermore, it has also been reported to be causes of certain orphan infections such as necrotizing metastatic abscesses involving the lungs, liver, spleen, brain, and lymph nodes. 3 , 4 Accumulating lines of evidence also indicate its role in pneumonia, 5 urinary tract infections, 6 meningitis, 7 endocarditis, and bacteria-associated hemophagocytic syndrome. 8 C. violaceum is resistant to a broad spectrum of antibiotics, especially beta-lactams like penicillin, ampicillin, and cephalosporins.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Furthermore, it has also been reported to be causes of certain orphan infections such as necrotizing metastatic abscesses involving the lungs, liver, spleen, brain, and lymph nodes. 3 , 4 Accumulating lines of evidence also indicate its role in pneumonia, 5 urinary tract infections, 6 meningitis, 7 endocarditis, and bacteria-associated hemophagocytic syndrome. 8 C. violaceum is resistant to a broad spectrum of antibiotics, especially beta-lactams like penicillin, ampicillin, and cephalosporins.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that C. violaceum is resistant to several antibiotics, mainly to some beta-lactams, but it is sensitive to others, such as carbapenems and quinolones ( Aldridge et al, 1988 ). Indeed, most of the treatments which were successful in controlling infections involved the use of the antibiotics ciprofloxacin and meropenem ( Nanayakkara et al, 2008 ; Ke et al, 2012 ; Campbell et al, 2013 ; Pant et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The tendency for the distribution of cases to be worldwide was maintained in our compilation, despite the most fatal cases having been described in developing countries (Supplementary Table S1 ). Moreover, recent reports of C. violaceum infection found that, in addition to systemic infections, this bacterium causes urinary tract infections and pneumonia in hospital environments, which raises concerns about its potential as a nosocomial pathogen ( Hagiya et al, 2014 ; Swain et al, 2014 ; Pant et al, 2015 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there were also three cases of nosocomial infections in the series-presumably due to selection pressure of broad-spectrum antibiotics-although this has been previously described. [18][19][20] In conclusion, despite isolation on 28 occasions in the past 21 years, there has not been a single death attributable to C. violaceum in our region. Severe disease is extremely uncommon, and even in the patients with infection, antibiotic therapy and simple supportive care is usually all that is required for cure.…”
mentioning
confidence: 60%